Ex.14.2 Q4 Factorization - NCERT Maths Class 8

Go back to  'Ex.14.2'

Question

 Factorise

(i) \(\begin{align}{a^4} - {b^4}\end{align}\)

(ii) \(\begin{align}{p^4} - 81\end{align}\)

(iii) \(\begin{align}{x^4} - {{(y + z)}^4}\end{align}\)

(vi) \(\begin{align}{x^4} - {{(x - z)}^4}\end{align}\)

(v) \(\begin{align} {a^4} - 2{a^2}{b^2} + {b^4} \end{align}\)

Text Solution

What is known:

Algebraic expression.

What is unknown:

Factorisation of the algebraic expression.

Reasoning: Use identity:

\[\begin{align}  & {{\left( a-b \right)}^{2}}={{a}^{2}}-2ab+{{b}^{2}} \\  & {{a}^{2}}-{{b}^{2}}=\left( a-b \right)\left( a+b \right) \\ \end{align}\]

Steps:

\(\begin{align}{\rm{(i)}}\quad {a^4} - {b^4} &= {{\left( {{a^2}} \right)}^2} - {{\left( {{b^2}} \right)}^2}\\&= \left( {{a^2} - {b^2}} \right)\left( {{a^2} + {b^2}} \right)\\&= (a - b)(a + b)\left( {{a^2} + {b^2}} \right)\end{align}\)

\(\begin{align}{\rm{(ii)}}\quad{p^4} - 81 &= {{\left( {{p^2}} \right)}^2} - {{(9)}^2}\\&= \left( {{p^2} - 9} \right)\left( {{p^2} + 9} \right)\\&= \left[ {{{(p)}^2} - {{(3)}^2}} \right]\left( {{p^2} + 9} \right)\\&= (p - 3)(p + 3)\left( {{p^2} + 9} \right)\end{align}\)

\(\begin{align}\left( {{\rm{iii}}} \right) \quad {x^4} - {{(y + z)}^4} &= {{\left( {{x^2}} \right)}^2} - {{\left[ {{{(y + z)}^2}} \right]}^2}\\&= \left[ {{x^2} - {{(y + z)}^2}} \right]\left[ {{x^2} + {{(y + z)}^2}} \right]\\ &= [x - (y + z)][x + (y + z)]\left[ {{x^2} + {{(y + z)}^2}} \right]\\&= (x - y - z)(x + y + z)\left[ {{x^2} + {{(y + z)}^2}} \right]
\end{align}\)

\(\begin{align}
\left( \rm{iv} \right)\quad {x^{\rm{4}}} - {{\left( {x - z} \right)}^{\rm{4}}} &= {{\left( {{x^2}} \right)}^2} - {{\left[ {{{\left( {x - z} \right)}^2}} \right]}^2}\\
&= \left[ {{x^2} - {{\left( {x - z} \right)}^{\rm{2}}}} \right] \left[ {{x^{\rm{2}}} + {{\left( {x - z} \right)}^{\rm{2}}}} \right]\\
&= \left[ {x - \left( {x - z} \right)} \right] \left[ {x + \left( {x - z} \right)} \right] \left[ {{x^{\rm{2}}} + {{\left( {x - z} \right)}^{\rm{2}}}} \right]\\
&= z\left( {2x - z} \right) \left[ {{x^{\rm{2}}} + {x^{\rm{2}}} - 2xz + {z^{\rm{2}}}} \right]\\&= z\left( {{\rm{2}}x - z} \right) \left( {{\rm{2}}{x^{\rm{2}}} - {\rm{2}}xz + {z^{\rm{2}}}} \right)\end{align}\)

\(\begin{align}({\rm{v}})\quad {a^4} - 2{a^2}{b^2} + {b^4} &= {{\left( {{a^2}} \right)}^2} - 2\left( {{a^2}} \right)\left( {{b^2}} \right) + {{\left( {{b^2}} \right)}^2}\\&= {{\left( {{a^2} - {b^2}} \right)}^2}\\&= {{\left[ {(a - b)(a + b)} \right]}^2}\\&= {{(a - b)}^2}{{(a + b)}^2}\end{align}\)

  
Learn math from the experts and clarify doubts instantly

  • Instant doubt clearing (live one on one)
  • Learn from India’s best math teachers
  • Completely personalized curriculum